MEMBANGUN KARAKTER IMAJINASI SISWA SEKOLAH DASAR MELALUI STORY TELLING UNTUK MENGEMBANGKAN LITERASI DI DESA SANGKANMULYA - Fitriyani, Yani; Putri Siti Nur Hawa Fadilah; Uhin Maftuhin; Firdaus Arsyad; Muhamad Irpan; Siti Sopiyaturrohmah; Ratu Censa Restu Kusuma (Abdimas Siliwangi, 2024)
The development of imaginative character in elementary school-aged children plays a crucial role in shaping their personality and cognitive intelligence. In Sangkanmulya Village, where access to educational resources is still limited, storytelling has become an effective educational tool for fostering students' literacy and imagination. This article discusses the structured implementation of storytelling activities at Sangkanmulya Village Elementary School, covering the preparation, execution, and expected outcomes. These activities involve collaboration between teachers, parents, and the local community to create an interactive and imaginative learning environment. Through storytelling, students not only improve their literacy skills but also develop positive character traits that prepare them for future challenges. Challenges in implementation, such as limited reading materials and teaching staff, are addressed through innovation and community participation. The article concludes with recommendations to expand storytelling practices as an educational tool in other areas with similar conditions.